Assessment of Enteric Fermentation Emissions in Ugandan Beef Production: Impact of Feeding Practices and Chloris Gayana Supplementation in Nakasongola and Mbarara district - Maholo, Denis Mulongo; Ogola, Clinton; Wamalwa, Kinyanjuyi; Massimo, Castiello (Open Science Journal, 2024)
The rising concentrations of greenhouse gases (GHGs) in the atmosphere pose a significant threat to global climate stability, primarily due to human activities. Agriculture, particularly animal production, contributes substantially to GHG emissions, with cattle production systems being a major contributor. In Uganda, where livestock plays a central role in the economy, there is a need to balance economic growth with environmental sustainability. Our study aims to evaluate and mitigate GHG emissions in Ugandan beef production, focusing on enteric fermentation emissions. By examining the impact of feeding practices, including Chloris gayana supplementation, we seek to identify strategies for emission reduction. Through meticulous data collection and analysis in Mbarara and Nakasongola districts, we observed significant effects of body weight, daily weight gain, breed, and feeding systems on various parameters related to energy, methane yield, and emission intensity. While Ankole cattle showed higher weight gain in Mbarara, Chloris Gayana supplementation increased methane emissions. In Nakasongola, both breed and feeding systems influenced weight gain and emission intensity. These findings emphasize the need for tailored mitigation strategies in the Ugandan beef industry to balance productivity and environmental sustainability. We recommend stakeholders reconsider current feeding and breeding practices to optimize both aspects, emphasizing the importance of sustainable practices for the industry's future.